The growth of intracluster light in XCS-HSC galaxy clusters from 0.1 < z < 0.5. Issue 2 (11th January 2021) - Furnell, Kate E; Collins, Chris A; Kelvin, Lee S; Baldry, Ivan K; James, Phil A; Manolopoulou, Maria; Mann, Robert G; Giles, Paul A; Bermeo, Alberto; Hilton, Matthew; Wilkinson, Reese; Romer, A Kathy; et al.
ABSTRACT: We estimate the intracluster light (ICL) component within a sample of 18 clusters detected in the XMM Cluster Survey (XCS) data using the deep (∼26.8 mag) Hyper Suprime-Cam Subaru Strategic Programme data release 1 i -band data. We apply a rest-frame μB  = 25 mag arcsec −2 isophotal threshold to our clusters, below which we define light as the ICL within an aperture of R X, 500 (X-ray estimate of R 500 ) centred on the brightest cluster galaxy (BCG). After applying careful masking and corrections for flux losses from background subtraction, we recover ∼20 per cent of the ICL flux, approximately four times our estimate of the typical background at the same isophotal level (${\sim}5{{\ \rm per\ cent}}$ ). We find that the ICL makes up about ${\sim}24{{\ \rm per\ cent}}$ of the total cluster stellar mass on average (∼41 per cent including the flux contained in the BCG within 50 kpc); this value is well matched with other observational studies and semi-analytic/numerical simulations, but is significantly smaller than results from recent hydrodynamical simulations (even when measured in an observationally consistent way). We find no evidence for any links between the amount of ICL flux with cluster mass, but find a growth rate of 2–4 for the ICL between 0.1 < z < 0.5. We conclude that the ICL is the dominant evolutionary component of stellar mass in clusters from z  ∼ 1. Our work highlights the need for a consistent approach when measuring ICL alongside the need for deeper imaging, in order to unambiguously measure the ICL across as broad a redshift range as possible (e.g. 10-yr stacked imaging from the Vera C. Rubin Observatory).